Arah Perkembangan Riset Kewirausahaan di Wilayah Pedesaan dan Perkotaan: Bibliometric Analysis - Edi Irawan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study explores the research trends on entrepreneurship in both rural and urban contexts from 2014 to 2025. Using a bibliometric analysis method, data were collected from the Publish or Perish database with the keywords “rural entrepreneurship” and “urban entrepreneurship.” The data were then analyzed and visualized using VOSviewer software to identify publication patterns, citation networks, and emerging research themes. The analysis indicates that entrepreneurship, both in rural and urban settings, contributes significantly to economic development, job creation, and social empowerment. Rural entrepreneurship studies often emphasize innovation in agriculture, the use of local resources, and community-based economic activities aimed at reducing poverty and migration to cities. Meanwhile, urban entrepreneurship research focuses more on technology-based innovation, start-up ecosystems, and creative industries that improve productivity and the quality of urban life. The findings also show a growing integration between rural and urban entrepreneurial ecosystems, suggesting that collaboration and knowledge transfer between the two regions can accelerate inclusive and sustainable development. This study provides valuable insights for policymakers, researchers, and practitioners to understand the evolution of entrepreneurship research and to design effective strategies for balanced regional development.